BAHASA PIDATO KAMPANYE: KAJIAN ANALISIS WACANA KRITIS - Hadi Saputro, Sueb (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
This research aims at describing, interpreting, and explaining (1) the theme/topic, (2) the structure (introduction, contents, closing), (3) the lexical meaning, (4) the sentential meaning, and (5) the intonation of campaigners of 2009 election campaign. This qualitative research used 2009 legislative and presidential campaign conducted in East Java region and presidential debate 2009 live from Trans TV Jakarta as its source of data. The data collection methods were observation, recording, field note taking, and interview. Data analysis were done during the research period, from the beginning until the end of the research. The result of the research showed that the theme raised by all president candidates is people’s prosperity improvement issue. The structure of campaign speech involved introduction in the form of heroic word “freedom” (Mega), polite word (SBY), compliments (JK). The content of campaign speech related only to temporary interest to gain power. Lexical and sentential meaning involved the study on three lexical values: experiential, relational and expressive value. The intonation of the campaign speech is generally raising intonation.